The Nexus of Human Intelligence and Technology in Information Sciences - Vahabi, Fataneh (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2025)
The advent of technology has revolutionized the field of information sciences, providing unique opportunities and challenges for scholars and practitioners alike. In this interdisciplinary domain, it is imperative to explore the intricate relationship between human intelligence and technology in furthering our understanding of information sciences. This essay aims to discuss how the convergence of human intelligence and technology has shaped the information sciences landscape, unraveling its profound implications for society.